The risk of oesophageal adenocarcinoma in a prospectively recruited Barrett's oesophagus cohort. Issue 6 (1st December 2016) - Theron, BT; Padmanabhan, H; Aladin, H; Smith, P; Campbell, E; Nightingale, P; Cooper, BT; Trudgill, NJ
Abstract : Background: Varying rates of oesophageal adenocarcinoma (OAC) complicating Barrett's oesophagus (BO) have been reported. Recent studies and meta‐analyses suggest a lower incidence, questioning the value of endoscopic surveillance. Aim: We aimed to retrospectively examine the rate of OAC, risk factors and causes of death in a prospectively recruited BO cohort. Methods: Data from patients with BO from a cohort from 1982–2007 were studied. Patients were subdivided into surveyed, failed to attend surveillance and unfit for surveillance. Standardised mortality ratios (SMR) were calculated for common causes of death. Cox proportional hazards models were used to determine which factors were associated with progression to OAC. Results: In total, 671 BO patients (61% male) were studied; 37 (76% male) were diagnosed with OAC. OAC incidence was 0.47% per annum and stable across three decades (1982–1991 0.56%, 1992–2001 0.46%, 2002–2012 0.41% ( p = 0.8)). All‐cause mortality was increased for the whole cohort (SMR 163(95% CI 145–183)). Mortality from OAC appeared higher in patients who failed to attend surveillance (SMR 3216(95% CI 1543–5916)) compared with surveyed (SMR 1753(95% CI 933–2998)) and those unfit for surveillance due to co‐morbidity (SMR 440(95% CI 143–1025)). Multivariable analysis identified low‐grade dysplasia (HR 4.4(95% CI 1.56–12.43), p = 0.005) and length of BO (HR 1.2(95% (1.1–1.3)), p < 0.001)) as associated with OAC. Conclusions: Progression to OAC appeared stable over three decades at 0.47% per annum. Patients with BO had a modest increase in all‐cause mortality and a large increase in OAC mortality, particularly if fit for surveillance. Low‐grade dysplasia and the length of the BO segment were associated with developing OAC.